SMART INNOVATION AND SUSTAINABLE TRANSPORTATION TECHNOLOGY TRANSFER FRAMEWORK FOR INTERCONNECTIVITY IN DEVELOPING COUNTRIES - Adewole OLADELE (Journal of Construction Project Management and Innovation)
Funding for research dissemination is increasingly uncertain which calls for trans-disciplinary and trans-sector research dissemination through collaboration in order to ensure that fundamental advances are made in the areas of focus for capacity building and sustainability of road infrastructure in Africa. Through dissemination of research, studies, publications on various disciplines, authoritative and non-partisan policy advice is being provided to decision makers in government, academia, and the private sector. Although, dissemination of research in road transportation is integral to our societies, there are persistent challenges to its sustainability. This paper proposes strategies for cooperation among academia, industry, and transport sector through transport research dissemination by establishment of transportation professional networking group to provide a platform for sharing of experiences and exchange of ideas amongst transport professionals and researchers. This group has organised four international conferences on transportation in Africa which required the dissemination of innovative researches and approaches that brought about safe and sustainable solutions. With proper coordination, transport experts are poised to help solve problems at this level of complexity and importance. The paper concludes by highlighting the availability of potentials and critical mass in academia, government and the private sector to attain global stature and tackle capacity building challenges in road transport sector which depends on how the research dissemination and publication ecosystem is nurtured.